Ulasan Elemen Kesihatan Mental Pekerja Wanita Sektor Perusahaan Kecil & Sederhana Malaysia melalui Kaedah Analisis Matrik - Zaidi, Nur Farhanis; Lee, Ming Foong (Online Journal for TVET Practitioners, 2020)
Mental health is defined as a state of well-being where an individual is aware of his or her own abilities, able to overcome the stress of life well, can work productively and contribute to the community. However, if these health problems are not properly addressed, it is not possible for these health issues to be at an alarming level and may affect the individual and other community members. Therefore, this article aims to review the mental health of female workers in the Small & Medium Enterprises (SMEs) sector in Malaysia. The objectives of this study were to explore the elements of mental health, explore the elements of dominant factors contributing to mental health problems, and to explore elements of effective methods for addressing mental health problems as part of a comprehensive set of instruments to assess the mental health of working in the SMEs sector. This study used matrix analysis methods to review the elements of mental health problems, factors contributing to mental health and effective ways of addressing the mental health problems of working women in Malaysian SMEs. A total numbers of 20 articles were reviewed to assess women’s mental health problems, 12 articles on factors contributing to mental health and 12 articles on effective methods. Findings show that mental health problems are stress, anxiety, depression, fear and anxiety; the key factor to mental health problems among SME sector women workers is family-work conflict, while effective ways to address mental health problems among SME sector women workers are counseling guidance.